Technical comparison of hybrid renewable energy systems for Information Technology services - John ADEBISI; Olumuyiwa Amusan; Ponmile Olawoore (Journal of Digital Food, Energy & Water Systems)
Several energy generations options that mitigate fossil fuel burning is currently being considered across the globe by various researchers to reduce atmospheric and environmental pollution, thus reducing the menace of negative climate change. There is a critical need for a technical comparison of an eco-friendly, cost effective, and near zero carbon foot-print for power solutions. Solar, wind and its hybrids can explored to meet the ever-increasing load demand of electrical power consumers especially in information technology (IT) services. Critical IT services and infrastructure are becoming unsustainable with a single power source hence the need for hybrid solutions. To overcome this problem, this research considers the efficiency of solar, wind and hybrid power. The novelty of this work is the information technology backup power requirement considered in the technical comparison.  The experimental result showed the input/output peak and off-peak voltages for solar, wind, and solar-wind hybrid energy DC-Volts are 12.67V/12.02V / 12.47V/11.61V, 12.53V / 11.90V / 12.48V / 11.87V, and 12.78V / 12.09V / 12.57 / 11.95V  respectively signifying a significant increase from the on-load peak period while the on-load off-peak period is seen to be lower. The results also show that a hybrid solar-wind system tested at 5 minutes time intervals gives a superior output voltage regulation and efficiency when compared to the solar or wind individual systems. It was concluded that the hybrid system of solar and wind energy source is an ideal standalone renewable energy power option in the university.